A service composition approach based on overall QoS and modified graphplan. (21st October 2019) - Zhu, Ming; Fan, Guodong; Li, Jing; Wang, Fengying
Increasing emphasis on users' preferences and the growth of services on the web make service composition a time consuming and complicated work. In this paper, an approach for web service composition that combines overall QoS and modified graphplan is proposed. Fuzzy logic is applied to handle uncertainty and support decision making. Specifically, values of overall QoS of services are generated by using fuzzy analytical hierarchy process, entropy and user's preferences. The graphplan is modified by pruning services according to the values of overall QoS of services in forward and backward expansions, while producing solutions of compositions. Furthermore, case studies and experiments are performed and show that our approach has better solutions compared with original graphplan and some other approaches.